Geobotanical classification of houseplants, ecology of main genera and species (Eurasian Scientific Herald, 2022)
Houseplants are ecologically pure plants that are widely used today for aesthetic pleasure. They are widely used in decoration. This article provides information on the origin of houseplants, their geobotanical classification, their growing conditions